Rescuing women from the brinks of whiteness: Carceral restoration in a human trafficking court - Singh, Rashmee (The British journal of criminology, 2024)
Research on gender-specific penal reform programs critique their failure to prioritize the socio-economic recovery of criminalized women. This paper draws on these insights to examine the Women’s Refuge Court (WRC), a human trafficking court for adult women criminalized for prostitution and drug offences in Ohio. Using ethnographic research, I illustrate the WRC’s rejection of bootstrapping and emphasis on material resourcing as a penal reform strategy. I argue that the WRC’s prioritization of socio-economic recovery derives from fears over the status decline of the impoverished white women who predominate as defendants. Court officials rely on evangelical Christian imaginings of prostitution as ‘modern day slavery’ to frame participants as ‘trafficking victims’. I identify the WRC’s response as a racially specific form of gender responsive programming called carceral restoration.